Perbandingan hasil pemeriksaaan metode zn dengan Metode genexpert pada penderita tuberculosis paru terhadap Pasien pengobatan selama enam bulan di rsud regional Provinsi sulawesi barat - Lutfi Lutfi; Muh Nur Ikhsan (Jurnal Media Laboran, 2020)
In 1995 the pulmonary tuberculosis eradication program was implemented with the DOTS strategy, one of the components in the DOTS strategy was OAT given for 6-8 months which is the most cost-effective health strategy. This study aims to determine whether there are still acid-fast bacilli (AFB) in the sputum of patients after intensive treatment for six months, which will be controlled through microscopic testing using Ziehl Neelsen staining with the concentration method.The results showed that from 15 samples of patients who had been treated with OAT, 12% were smear positive (2 samples) and 26% were Genexpert (15 samples). And the results of the examination are suggested to patients with positive test results, the treatment should be continued